6x+y=-3

Subtract 6x from both sides of the equation.

y=-3-6x

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Reorder -3 and -6x.

y=-6x-3

y=-6x-3

Find the values of m and b using the form y=mx+b.

m=-6

b=-3

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: -6

y-intercept: -3

Slope: -6

y-intercept: -3

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=-6⋅0-3

Simplify the result.

Multiply -6 by 0.

f(0)=0-3

Subtract 3 from 0.

f(0)=-3

The final answer is -3.

-3

-3

The y value at x=0 is -3.

y=-3

y=-3

Choose 1 to substitute in for x to find the ordered pair.

Replace the variable x with 1 in the expression.

f(1)=-6⋅1-3

Simplify the result.

Multiply -6 by 1.

f(1)=-6-3

Subtract 3 from -6.

f(1)=-9

The final answer is -9.

-9

-9

The y value at x=1 is -9.

y=-9

y=-9

Create a table of the x and y values.

xy0-31-9

xy0-31-9

Graph the line using the slope and the y-intercept, or the points.

Slope: -6

y-intercept: -3

xy0-31-9

Graph 6x+y=-3